Children's palliative care: examination of a nursing rotation programme. (2nd February 2021) - Whiting, Lisa; Whiting, Mark; Petty, Julia; O'Grady, Michele
Abstract : Background: An 8-month rotation programme was implemented for five nurses employed in two kinds of children's palliative care environments: hospital wards and hospices. This study reports the views of the nurses completing the rotation. The research drew on appreciative inquiry and involved a pre- and post-rotation interview and questionnaire. Thematic analysis of the interviews revealed seven themes: adjusting to the rotation programme; support mechanisms; being safe; new knowledge and skills; knowledge exchange; misconceptions; future plans. These were supported by the questionnaire findings. Although the nurses identified some frustration at having to undertake competency assessments relating to previously acquired skills, as well as being out of their 'comfort zone', all the participants highly recommended the programme. They commented very positively on the support they received and the overall learning experience as well as the new insight into different aspects of care. In addition, they were able to share their newfound knowledge and expertise with others.